Political geography I: Agency. (February 2019) - Kuus, Merje
This report focuses on human agency – the capacity to act in a given context – as it is studied and reflected upon in political geographic research. I first discuss the investigations of agency in the wide-ranging work on political subjectivity and identity formation. The report then turns to the efforts to trace ideas and things in political processes. I showcase the attention to transnational networks and fields as well as the work inspired by the concepts of assemblage and actor-network. The analysis finally turns to questions of method in the study of political agency as I foreground the growing interest in ethnography, emotions, and ethics in the sub-discipline. No amount of conceptual innovation, I conclude in the final section, can substitute for the careful study of inherently difficult political issues in specific social settings. In order to effectively problematize the boundaries between politics and culture, subject and object, state and non-state institutions, or public and private spheres, research must closely consider the contingent and situational character of these categories.